PERANCANGAN MEDIA KOMUNIKASI VISUAL UNTUK MEMPROMOSIKAN GRAND OPENING TOKO ALFAMART GUNUNG SANGHYANG 270 - Gaita Salam, Ethan; Wirawan, I Gusti Ngurah; Putra, Gede Bayu Segara (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
PT Sumber Alfaria Trijaya Tbk. Bali Branch has the aim of introducing the company's image through the Grand Opening of Alfamart stores in various areas of Bali so that it is present and affordable closer to consumers. Currently the growth of Alfamart Bali Branch in opening outlets in every corner of Bali is increasing, one of which is the Grand Opening of Alfamart Gunung Sanghyang 270 on Jl. Gunung Sanghyang, Kel. Kerobokan Kaja, Kec. North Kuta, Kab. Badung, Bali which was held on October 18, 2023. So the role of a Visual Communication Design (DKV) student who can design promotional media by applying the concepts or theories that have been learned while participating in learning on campus is needed. By conducting interviews, observation, and documentation methods to obtain data that helps in carrying out real projects such as the Grand Opening of Alfamart Gunung Sanghyang 270 store, promotional media can be used to expand the target market and build public awareness of the existence of the nearest Alfamart.